Epidemiological role of plant pigment bixin in adipaging: In vivo pilot study - Leepica Kapoor; Siva Ramamoorthy (Clinical Epidemiology and Global Health, 2022)
Background: Obesity and aging are linked in a cross talk, a phenomenon known as “Adipaging”. Here, we emphasize the similarity in the underlying mechanisms of obesity and aging and propose the probability of obesity being a risk factor for premature aging. In current times, several side effects of chemical usage in pharmaceuticals used for combatting adipaging have been reported. Thus, search for plant-based bioactive compounds as nutraceuticals against adipaging is the need of the hour. Methods: Bixin, an FDA approved food additive and pigment derived from the plant Bixa orellana L. has been studied for its potential beyond a food colourant as a nutraceutical in targeting adipaging in vivo. Dual-energy X-ray absorptiometry (DXA) scan was used as a tool to study the impact of bixin supplementation on body composition of photoaged C57BL/6 mice. Results: On comparing the DXA scans pre and post treatment with bixin in photoaged mice, statistically significant and dose dependent impact of bixin among various treatment groups of mice was observed with an increase in mean difference in lean mass ranging from 2.83g (B+ low dose (100 mg/kg of bixin)), to 2.86g (B++ medium dose (250 mg/kg of bixin)) and 3.73 g (B+++ high dose (500 mg/kg of bixin)). Also, a decline in mean difference in fat mass from −0.53g (B+), −0.33g (B++) and −1.033g (B+++) was observed with increasing bixin dosage. Conclusion: DXA highlights the protective role of bixin on metabolic health and a probable target as an anti-adipaging nutraceutical.